From understanding to habituation: Teachers’ three pedagogical roles in fostering students’ social care through the Friday Charity program - Nurul Huda; Nurul Cholisah; Abdulmumin Musa Omiya (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2026)
Developing students’ social concern remains challenging, particularly in transforming their understanding of values into concrete behaviors and sustained habits. This challenge requires teachers to perform systematic pedagogical roles through instruction, guidance, and habituation. This study aims to analyze teachers’ roles in fostering students’ social concern through the Jumat Beramal (Friday Charity) Program. Specifically, it examines teachers’ roles as instructors, mentors, and trainers in developing value-based understanding, facilitating social practices, and cultivating the habits of sharing, empathy, and responsibility. The study employed a qualitative case study design at Ulul Albab Elementary School in Jember, Indonesia. Data were collected through observations, in-depth interviews, and documentation involving the school principal, classroom teachers, and purposively selected students. The data were subsequently analyzed using thematic analysis, while data credibility was ensured through source and methodological triangulation. The findings reveal that teachers perform three interconnected pedagogical roles: as instructors who develop students’ understanding of social concern, as mentors who facilitate the application of values through social practices, and as trainers who cultivate habits of sharing through active, repeated participation. The study concludes that integrating these three roles creates a pedagogical cycle that transforms social concern from a value-based understanding into internalized prosocial behavior. This study contributes conceptually by demonstrating that character education requires integrated instruction, guidance, and habituation through sustained social experiences. Practically, the findings inform elementary schools in designing character education programs that connect classroom learning with authentic social practices.